(untitled) (Journal of Engineering Science, 2023)
Overcrowding, poor structural quality of housing, and a lack of basic services and infrastructure differentiate informal settlement as a distinct type of community. Poor housing quality is directly connected to a greater risk of disease and illness in informal settlements. This research is being carried out to provide a comprehensive picture of the existing physical conditions of housing and aims to measure the deviation of housing quality between existing and standard healthy housing parameters in informal settlements. A substantial amount of fieldwork has been conducted to map the existing physical structure of the settlement and a list of preventable diseases suffered from poor housing is made through conducting a focus group discussion and interviews of 50 households in a distinct informal settlement situated in Bangladesh’s third-largest city, namely Khulna. To assess the housing quality a framework of standard housing is made by reviewing the book “Park’s textbook of preventive and social medicine” by K. Park. Results indicate that - 70% of the total household does not satisfy the minimum housing standard; in most cases, 4 or 5 persons must share a single room of 102 to 150 sqft area; a single toilet serves 180 people; the queuing time for drinking water from a tube well exceeds 45 minutes. The study also reveals the settler’s complex mechanism of compact living through space sharing dynamics. Journal of Engineering Science 13(2), 2022, 51-67